Clinical evaluation of a transmission detector system and comparison with a homogeneous 3D phantom dosimeter. (February 2019) - Giglioli, Francesca Romana; Gallio, Elena; Franco, Pierfrancesco; Badellino, Serena; Ricardi, Umberto; Fiandra, Christian
Highlights: No correlation was found between Dolphin DVHs analysis and Delta 4 γ passing rate. A value of 10.7% ± 0.7% was found for detector attenuation. Correlation was found between γ inside the PTV (Dolphin) and clinical decision. Abstract: Purpose: To evaluate the performances of the Dolphin system for pre-treatment verification (IBA Dosimetry, Schwarzenbruck, Germany) based on transmission measurements, employing a clinical perspective. Methods and materials: Fifty treatment plans were verified by Dolphin and Delta 4 detectors (Scandidos, Uppsala, Sweden) during the same session and subsequently by the Delta 4 itself. The attenuation factor of the transmission detector (required for on-line dosimetry) was evaluated by comparing Delta 4 measurements with and without Dolphin. Gamma evaluation was performed to compare the plan dose with the one delivered in case of Delta 4 and Dolphin (gamma analysis within the structures). Dose–volume based parameters for PTV and OARs doses were considered for Compass calculation and Dolphin reconstruction and clinical decisions were made by two expert physicians in order to assess the "pass", "fail" or "evaluate" grade of the treatment plans. A statistical analysis was performed to investigate the eventual correlation between Delta 4 gamma analysis and Dolphin clinical evaluation. Results: A value of 10.7% ± 0.7% was found for detector attenuation. No patients were classified as "fail" by the two instruments as well as by physicians. No correlation was found between the Delta 4 gamma metric and physician classification; conversely, a significant correlation was observed for Dolphin between the numbers of points with gamma ≥1 (gamma failure rate, as evaluated by the Dolphin) in the PTV area and clinical decision. Conclusion: The Dolphin system demonstrated to be an accurate detector for pre-treatment purposes and could be used as a clinical decision making tool for plan acceptance.